Derrida vs Husserl—about the Shortcomings of Deconstruction of Phenomenology - Moryń, Mariusz (Sensus Historiae, 2023)
The subject of this article is Jacques Derrida’s critique of Edmund Husserl's transcendental phenomenology. I intend to demonstrate that it contains a number of shortcomings and misses the essence of the position it questions. The Derridean reading of Husserl’s writings, although based on complex and subtle interpretations, misses the message of the original phenomenological treatises. Consequently, this calls into question the significance and value of deconstruction as well as raises the question of which work by Husserl was dismantled and whether it was the most valuable text in terms of content. Should the reading made by the French philosopher and the conclusions drawn from it be treated as particularly distinctive? In the following considerations, I support a different, let’s call it “traditional,” non-deconstructed reading of the phenomenological concept—I treat them as philosophically more promising and more interesting.